Representations of the world in language textbooks - Risager, Karen 1947- (Bristol, UK Multilingual Matters, 2018)
"This book presents a new and comprehensive framework for the analysis of representations of culture, society and the world in textbooks for foreign and second language learning. It points to the need for language learning materials to deal seriously with knowledge about the world, including its diversities and problems"--Provided by publisher.
Representations of the world -- Culture in textbook analyses around the world -- National studies -- Citizenship education studies -- Cultural studies -- Postcolonial studies -- Transnational studies.
Includes bibliographical references (pages 230-246) and indexes.
Keywords: Language and languages -- Textbooks -- Evaluation; Cultural pluralism in textbooks; Multicultural education; Language and culture